Transforming Pharmacovigilance Using Gen AI: Innovations in Aggregate Reporting, Signal Detection, and Safety Surveillance - Praveen, John; Kumar CM, Krishna; Channappa, Ajay Haralur (The Journal of Multidisciplinary Research, 2023)
Pharmacovigilance, the science of monitoring and evaluating drug safety, plays a crucial role in ensuring patient well-being and public health. With the advent of artificial intelligence (AI), specifically Gen AI, pharmacovigilance has witnessed a transformative shift. Gen AI's advanced capabilities in real-time signal detection, automated reporting, and data integration have significantly enhanced the efficiency and accuracy of drug safety monitoring and surveillance.This article explores the role of Gen AI in pharmacovigilance, emphasizing its potential to revolutionize aggregate reporting, signal detection, risk assessment, and safety surveillance. It delves into the challenges and considerations that come with adopting AI in pharmacovigilance, such as ethical and regulatory implications, data privacy and security concerns, and the need for algorithm transparency and interpretability.The article also discusses the future directions and opportunities for Gen AI in pharmacovigilance which include enhanced signal detection algorithms, personalized safety assessments, and predictive risk modelling and incorporation of emerging technologies like blockchain and IoT that can complement Gen AI and improve data security and real-time monitoring.Collaborative efforts and data sharing among stakeholders are essential for maximizing Gen AI's potential in pharmacovigilance. Public-private partnerships and global pharmacovigilance networks can accelerate the adoption of AI technologies and drive innovation in drug safety monitoring.In conclusion, Gen AI presents a transformative opportunity for pharmacovigilance, promising safer medications and improved patient outcomes. Embracing responsible AI adoption, addressing ethical considerations, and encouraging further research are key to unlocking the full potential of Gen AI in advancing drug safety and public health.